2005
DOI: 10.1080/00140130400029092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of button location on driver's visual behaviour and safety perception

Abstract: Although buttons are a frequently used type of control in car interiors, little research has been undertaken on how the usage of buttons affects the visual behaviour of the driver. In this study, the aim was to analyse the effect of push button location and auditory feedback on drivers' visual time off road and safety perception when driving in a real traffic situation. The effect of six button locations (five on the centre stack, one near the gear stick) was tested. Drivers' visual behaviour was studied in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 5 publications
2
12
0
1
Order By: Relevance
“…Although Dukic [12], [13] did not use an integrated switch, they predicted, on the basis of their results, that the integrated switch should be installed on the drivers' side from the viewpoint of decreasing time off road.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although Dukic [12], [13] did not use an integrated switch, they predicted, on the basis of their results, that the integrated switch should be installed on the drivers' side from the viewpoint of decreasing time off road.…”
Section: Introductionmentioning
confidence: 93%
“…Dukic et al [12], [13] showed that the switch (control) location close to the gear stick and with highest eccentricity produced a shorter time off road (the time period when drivers look aside). Although Dukic [12], [13] did not use an integrated switch, they predicted, on the basis of their results, that the integrated switch should be installed on the drivers' side from the viewpoint of decreasing time off road.…”
Section: Introductionmentioning
confidence: 98%
“…Poorly designed button placement and touchscreen buttons require the driver to glance momentarily at the display to confirm choice [7]. It is shown that the visual time off road increases significantly as the angle increases between the normal light of sight while driving and the button location [26]. This is especially disconcerting as touchscreens seem to be migrating to vehicles as the interaction display of choice, presumably because of the readily-available hardware and software technology from existing smart phones and tablets.…”
Section: The Input Perspectivementioning
confidence: 99%
“…Eye tracking is a method that registers the movement of human gaze for instance when reading text, when driving a car, working on the internet, or as part of evaluating psychiatric disorders or investigating the workload of air traffic controllers [17][18][19][20][21][22] . Eye tracking has been used in radiology, mainly to analyse the way radiologist read mammograms [23][24][25][26][27] but also how different viewing procedures influence the efficiency of reading CT images of the lung 28 .…”
Section: Introductionmentioning
confidence: 99%